Restorative Justice the Limitations of Authority of Police and Prosecutors in the Criminal Justice System - Satriadi Satriadi (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2022)
This study discusses the limits of authority of the police and prosecutors in implementing restorative justice in criminal cases. The Indonesia National Police, the Attorney General Office of the Republic of Indonesia, have implemented the principle of restorative justice as a form of dealing with criminal cases. The Indonesian National Police makes further regulations for each law enforcement agency with the principle of restorative justice which will be used as a guide in handling criminal cases, including Circular Letter of The Chief of Indonesia National Police No. SE/8/VII/2018 of 2018, The Chief of Indonesia National Police Regulation No. 6 of 2019, the Attorney General Regulation No. 15 of 2020. To analyze and understand restorative justice and the limitations of the police and prosecutor's authority in the criminal justice system, this study uses a normative legal research method, the data obtained through a literature study. The results show that restorative justice must be accompanied by an understanding of the concept of police discretion, because there is a relationship between discretion and restorative justice. The statement of reconciliation between the perpetrator and the victim contained in the statement letter should be the basis for investigators to terminate the investigation (SP3) other than those stipulated in Article 109 of the Criminal Procedure Code and the case is considered completed in Law Number 16 of 2004 concerning the Attorney Office of the Republic of Indonesia, in Article 35 letter c. The Attorney General of the Republic of Indonesia has released a regulation concerning Termination of Prosecution Based on Restorative Justice as contained in the Attorney General Regulation Number 15 of 2020. Based on this regulation, the public prosecutor has a strong legal basis for terminating prosecution of defendants in certain criminal acts and if between the victim and the defendant have an agreement to make peace.